1998
DOI: 10.1007/s004670050523
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonaemia due to Klebsiella infection in a neuropathic bladder

Abstract: A boy with a neuropathic bladder and a single hydronephrotic kidney developed hyperammonaemic encephalopathy during a urinary tract infection with Klebsiella oxytoca. Although particularly associated with Proteus infections and prune belly syndrome, hyperammonaemia can complicate infection with any urease-producing bacteria if there is urinary stasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Secondly, Corynebacterium spp. was only reported once in a similar condition [6], the other isolated pathogens being Proteus mirabilis [3,4,7,8], Klebsiella oxytoca and Klebsiella pneumoniae [1,2,3], Enterococcus faecalis [1], Moraxella catarrhalis [1] and Enterobacter [3]. Thirdly, elevated plasma glutamine points to prolonged hyperammonaemia, but normalisation of plasma ammonia within a few hours of therapy is inconsistent with a primary metabolic disorder.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Secondly, Corynebacterium spp. was only reported once in a similar condition [6], the other isolated pathogens being Proteus mirabilis [3,4,7,8], Klebsiella oxytoca and Klebsiella pneumoniae [1,2,3], Enterococcus faecalis [1], Moraxella catarrhalis [1] and Enterobacter [3]. Thirdly, elevated plasma glutamine points to prolonged hyperammonaemia, but normalisation of plasma ammonia within a few hours of therapy is inconsistent with a primary metabolic disorder.…”
Section: Discussionmentioning
confidence: 93%
“…Proteus mirabilis, Klebsiella oxytoca and Klebsiella pneumoniae and Corynebacterium group D-2, has been reported in a few children with known underlying obstructive uropathy [1,2,3,4,5,6,7,8,9,10]. Three concurrent pathogenetic mechanisms are known to cause hyperammonaemia secondary to UTI: (1) infection with urease producing organisms splitting urea into ammonia [1,2,3,4,5,6,7,8,9,10], (2) slow passage of large urinary volumes along a large mucosal surface area [6], and (3) an alkaline urinary pH favouring diusion of ammonia into the blood stream [3,5,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Her high ammonia level is thought to have resulted from the production of excessive amounts of ammonia within the over distended bladder. [2][3][4][5][6][7][8][9] Ureasplitting bacteria produce urease in UTIs and the hydrolysis of urinary urea to ammonium and carbon dioxide results in highly alkalinized urine. Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella species, Morganella morganii and Corynebacteria are the best known urea-splitting bacteria, but Enterococcus faecium also produce urease.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, non-hepatic hyperammonaemic encephalopathy had been reported in some patients with urea-splitting urinary tract infections. [2][3][4][5][6][7][8][9] In particular, recurrent hyperammonaemic encephalopathy had been reported in patients with urinary diversion or vesico-colonic fistula. 2,3 However, simple urinary tract infection (UTI) and urinary retention without appropriate treatment might be associated with recurrent hyperammonaemic encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge approximately 20 children have been reported in the literature with this particular condition. All of these cases had predisposing conditions: prune belly [3][4][5][6][7], hydronephrosis [8,9], ureterocele [8], anti-reflux surgery or other urological intervention [10,11]. Murray et al reported infection with Providencia rettgeri, not previously described as a causative organism [6].…”
mentioning
confidence: 97%